Barriers to Postpartum Follow-Up and Glucose Tolerance Testing in Women with Gestational Diabetes Mellitus - Battarbee, Ashley N.; Yee, Lynn M. (American Journal of Perinatology, 2018)
Objective This study aims to examine factors associated with postpartum follow-up and glucose tolerance testing (GTT) in women with gestational diabetes mellitus (GDM).Materials and Methods Case-control study of women with GDM at a single institution with available outpatient records (January 2008–February 2016). Women with pregestational diabetes mellitus were excluded. The postpartum follow-up, GTT completion, and the reason for GTT completion failure (provider vs. patient noncompliance) were assessed. Bivariable and multivariable analyses were performed to identify factors associated with postpartum follow-up and GTT completion.Results Of 683 women, 82.0% (n = 560) returned postpartum, and 49.8% (n = 279) of those completed GTT. Women with Medicaid and late presentation to care were less likely to return (adjusted odds ratio [aOR]: 0.3, 95% confidence interval [CI]: 0.2–0.6 and aOR: 0.4, 95% CI: 0.2–0.7), but if they did, both factors were associated with increased odds of GTT completion (aOR: 2.0, 95% CI: 1.3–2.9 and aOR: 3.5, 95% CI: 1.8–6.6). Patient and provider noncompliance contributed equally to GTT completion failure. Trainee involvement was associated with improved test completion (aOR: 4.6, 95% CI: 2.4–8.8).Conclusion The majority of women with GDM returned postpartum, but many did not receive recommended GTT. Public insurance and late presentation were associated with failure to return postpartum, but better GTT completion when a postpartum visit occurred. Trainee involvement was associated with improved adherence to screening guidelines.
Keywords: gestational diabetes mellitus; glucose tolerance test; postpartum